Manage Employee Work Stress with Group Counseling Intervention - Ardiani, Rahma; Qatrunnada, Rizqi Zulfa (Prosiding University Research Colloquium, 2021)
This research aims to determine the group counseling intervention to manage work stress of PT D’s production executives during the application of work from office policies during pandemic. This study uses a quantitative method with a questionnaire instrument. The scale used is 14 items measuring the CD-RISC resilience variable and 9 items measuring the DASS work stress variable. The sampling technique used is purposive sampling. Respondents amounted to 45 people. The data analysis technique used Pearson Product Moment correlation. The results showed that there was an insignificant relationship between resilience and work stress of PT D production executives. It can be concluded that resilience is not the main factor in dealing with work stress. Researchers give recommenation intervention held a group counseling to decrease work stress impact.